High‐Precision Ionic Thermocouples Fabricated Using Potassium Ferri/Ferrocyanide and Iron Perchlorate. (4th January 2022) - Jeon, Jei Gyeong; Kim, Hyeong Jun; Shin, Gilyong; Han, Yusu; Kim, Ju Hyeon; Lee, Ju Hwan; Lee, Junho; Lim, Hyeoncheol; Ha, Seulki; Bae, Minwoo; Yoon, Sang‐Hee; Kang, Tae June
Abstract: A thermocouple is the most widely used electrical component for cost‐effective measurement of temperature in both academia and industry. However, its low sensitivity with typically tens of microvolts per Kelvin needs to be improved to obtain precise measurements. Introduced here is an ionic thermocouple to provide the level of accuracy required of temperature measurements in medicine, precision agriculture, smart buildings, and industrial processes. Ionic conductors are utilized in place of the electrical conductors typically used in the conventional thermocouples (TCs). The ionic thermocouples (i‐TCs) are demonstrated with redox reactions of 10 × 10 −3 m potassium ferri/ferrocyanide and 0.7 m iron(II/III) perchlorate, which are electrolytes used as p‐type and an n‐type elements, respectively. The voltage output of the i‐TC that is generated by a change in temperature is approximately two orders of magnitude larger than that of the conventional TC, providing almost two more significant figures in measured temperature. The i‐TC can easily be miniaturized as demonstrated for the in situ temperature measurement of the fluid flowing in the channel of a microfluidic device. A flexible and stretchable i‐TC device is also demonstrated to stably operate up to a tensile strain of 23% with no noticeable degradation in performance. Abstract : Ionic thermocouples (i‐TCs) are fabricated using potassium ferri/ferrocyanide and iron perchlorate. The voltage output of this i‐TC that is generated by a change in temperature is approximately two orders of magnitude larger than that of the conventional TC, providing almost two more significant figures in measured temperature.